Tratamento interdisciplinar e inter-relações entre Matemática e Física: potencialidades e limites da implementação dessa perspectiva - Martins, Douglas Aparecido Nacci (2005)
The objective of the present work is to research the interdisciplinary treatment as one of several alternatives of curricular organization, in discussion today, by analysing the available literature about this theme, the position of the experts, and the conditions of implemeting, relating to the teachers formation and didactic available material. This work is inserted in the research line of Mathematics in the curricular organization: history and present perspectives , of the Posgraduated Study Programme in the Mathematics Education of PUC/SP, and integrates the research project denominated Curricular Innovations in the Fundamental and High School , coordinated by Prof. Dr. Célia Maria Carolino Pires, a research ensemble of which the thematic center is the curricular organization of the Fundamental and High School. Our purpose is to gather several elements to reflection about the possibilities and borders of this perspective of organization and curricular development in High School, by focalizing the interrelations between Mathematics and Physics. We take as basis differente authors, in special Sacristan, Doll, Pires and Moreira, to investigate the ways how the idea of interdisciplinarity appears in the debate about curricular organization. We interview two mathematical educators and one expert in Physics teaching, who were invited to expose their ideas about the possibilities and boundaries of this proposal. At last, we analyse the points of views of a group of High School teachers, about the utilization of proposals to the interdisciplinary work and the High School didatic books analysed by MEC, in the Didactic Book National Programme to the High School, focalizing if and how the approachments interdisciplinary are present and, in particular, how the articulation between Mathematics and Physics occurs. We verify the existence of a convergence of principles pointed in the earliest literature about education curriculum and the position of experts and High School teachers as for the importance of interdisciplinary approachments. Besides, the formation of teachers and the characteristics of didactic books are still turning points to preponderate antique, disconnected linear practices